Understanding the rural third sector: insights from Veblen and Bogdanov - Vladislav Valentinov (Kybernetes, 2012)
Purpose: Despite the worldwide importance of third sector organizations in rural areas, the theoretical connection between the third sector and rural development remains largely unexplored. The purpose of this paper is to develop a theoretical explanation of why and how third sector organizations contribute to rural development. Design/methodology/approach: The paper builds upon the institutional economics of Thorstein Veblen and the tektology of Alexander Bogdanov. Tektology is used as an instrument to bring Veblenian criticism of pecuniary culture to bear on the explanation of the rural third sector. Findings: Based on the tektological law of systems divergence, the Veblenian pecuniary-industrial dichotomy and rural-urban disparities are shown to be interrelated evolutionary consequences of pecuniary culture. Third sector organizations' contribution to rural development is explained in terms of the tektological notion of counter-differentiation. Applied to pecuniary culture, counter-differentiation involves attenuating its basic ingredients, such as private ownership and pecuniary motivation. This is achieved through third sector organizations' characteristics such as profit appropriation constraint and nonpecuniary goal orientation, respectively. Originality/value: The paper identifies the institutional economics implications of the general systems theory and utilizes these implications to inform the research on the internationally relevant problem of rural development.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich. - This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively
Keywords: 330; systems theory; rural economies; third sector; rural development; tektology; institutional economics; Veblen; Bogdanov